What role does serious mental illness play in mass shootings, and how should we address it? - Skeem, Jennifer L. (Criminology & public policy, 2020)
Research A popular explanation for mass shootings is that the assailant "must have been mentally ill." A popular policy solution is exceptionalist—enter more gun-disqualifying psychiatric records into the background check system to keep guns away from identified people with mental illness. We synthesized research on the connection between mental illness and common violence, gun violence, homicide, and mass violence. We focused on serious mental illnesses like schizophrenia, bipolar disorder, and major depression, which are not the same as emotional distress from life circumstances and problematic personality traits. We found an association between serious mental illness and violence, but it is weaker than the public imagines or the media portrays, and rarely causal. Serious mental illness plays a limited role—it is neither a necessary nor a sufficient condition for mass violence. Policy Implications Exceptionalist policies in which serious mental illness is assumed to cause mass shootings will do little to prevent them—and will subject millions of nonviolent people with mental illness to stigma and unwarranted social control. Mass violence is a multidetermined problem. Because major risk factors for violence are shared, improvements in policies designed to keep guns out of the hands of dangerous people without mental illness will also go far in preventing incidents involving those with mental illness. Chiefly, these steps include sharpening the criteria for gun disqualification and temporarily removing guns from individuals at imminent risk for violence. The implementation of threat assessment teams and funding for crisis services for people with and without mental illness may also be helpful.